Broadband wave-absorbing metamaterial with robust topological gradient structure
By designing a wide-band wave-absorbing metamaterial with robust topological gradient structure, using the three-layer gradient structure and regular hexagonal blind holes, the problem of poor absorption of electromagnetic waves in the existing metamaterial is solved, and efficient absorption and regulation of the wideband is achieved.
Patent Information
- Application Number
- CN202510084840.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing step-type metamaterials have poor absorption effect on electromagnetic waves, resulting in a narrow absorption bandwidth.
A broadband absorbing metamaterial with a robust topological gradient structure was designed, using a three-layer gradient structure with a regular four-sided platform structure, and a regular hexagonal blind hole was set up in the center of the upper surface of the absorbing layer. The material was mixed with aerogel and paraffin.
It achieves a wider effective absorption bandwidth, reaching 38GHz, breaking through the narrow absorption bandwidth problem of traditional absorbing materials, and effectively absorbing electromagnetic waves in different frequency ranges.
Smart Images

Figure CN119786987A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a broadband wave-absorbing metamaterial with a gradient structure. Background Art
[0002] With the continuous development of science and technology, the requirements for material performance are increasing. Traditional materials are gradually unable to meet the special needs in some aspects such as high-performance electromagnetics, optics, acoustics, etc. Metamaterials, as a new type of artificial composite material, have received extensive attention and research due to their unique structure and performance. However, the existing metamaterial design still has certain limitations in terms of performance optimization and compatibility of preparation processes. Simple gradient stacking cannot give full play to the advantages of metamaterials in the field of electromagnetic wave absorption. Therefore, it is imperative to further improve and innovate structural design to achieve more efficient, stable and multifunctional metamaterial applications.
[0003] It is becoming increasingly important to integrate the structural design of metamaterials into the field of electromagnetic wave absorption. For example, Ye et al. prepared a stepped structure absorber. The absorber consists of four layers. The bottom layer is a plate with periodic square holes, and the upper layer is a periodic distribution of three cubes with equal thickness and gradient length of the side. The results show that the minimum reflection loss (RL min) is -36.01dB, and the effective absorption bandwidth (EAB) is 12.75GHz (Chao Yang, Enyi He, Peng Yang, QiGao, Tangming Yan, Xiaoong Ye, Yongsheng Ye, Haihua Wu. 3D-printed stepped structure based on graphene-FeSiAl composites for broadband and wide-angle electromagnetic wave absorption. Composites Part B: Engineering, 2024, 270: 111135). Chen et al. optimized the macroscopic structure of the absorber through gradient design, and successfully extended the effective absorption bandwidth to 11.81GHz by introducing multiple interferences (Ruiyang Tan, Fangkun Zhou, Ping Chen, BaoshanZhang, Jintang Zhou. PANI / FeCo@C composite microspheres with broadbandmicrowave absorption performance. Composites Science and Technology, 2022, 218: 109143). The above studies show that metamaterials designed with gradients are an effective way to broaden the bandwidth of electromagnetic wave absorption. Metamaterials can break through the performance bottleneck of traditional materials with their unique design structure. By carefully constructing the microstructure, precise control of electromagnetic waves can be achieved, thereby achieving efficient electromagnetic wave absorption in a specific frequency band or a wide frequency range, bringing new hope and possibilities for solving many problems in the modern electromagnetic environment, and becoming a highly promising research and application direction in the field of electromagnetic wave absorption. Summary of the invention
[0004] The present invention aims to solve the technical problem that the existing stepped structure metamaterial has poor electromagnetic wave absorption effect, and provide a broadband wave absorbing metamaterial with a topological gradient structure having robust characteristics.
[0005] The broadband absorbing metamaterial with a topological gradient structure having robust characteristics of the present invention is composed of a reflecting layer located at the bottom and an absorbing layer located at the top, wherein the absorbing layer is composed of three-layer gradient structures, all of which are regular tetrahedral structures, and the bottom side length of the upper prism is smaller than the top side length of the lower prism, and the central axes of the three-layer gradient structures coincide; a regular hexagonal blind hole is arranged at the center of the upper surface of the absorbing layer, and the depth of the blind hole is smaller than the depth of the regular tetrahedral structure of the top layer; and the absorbing layer is formed by mixing aerogel material and paraffin.
[0006] The specific periodic structure of the metamaterial can produce multiple responses to electromagnetic waves. The present invention can satisfy the λ / 4 attenuation model of multiple thicknesses by adjusting the thickness of each layer in the stepped structure, thereby generating multiple absorption peaks. Each band has a different center frequency and bandwidth, allowing electromagnetic waves to be effectively absorbed in different frequency ranges. The superposition of these bands in the overall stepped structure can achieve a wider EAB.
[0007] Compared with traditional absorbing materials, the broadband absorbing metamaterial with a robust topological gradient structure designed by the present invention not only breaks through the problem of narrow absorbing bandwidth, but also achieves a wider bandwidth of 38 GHz compared with other gradient-designed metamaterials. This is due to the following two points:
[0008] 1. The sides of the absorbing layer are all inclined planes, with an angle of 18° to 30° with the vertical plane. The inclined planes will cause more reflections, refractions and scattering of electromagnetic waves inside the metamaterial structure, thereby increasing the propagation path and interaction time of electromagnetic waves in the material, resulting in greater attenuation of electromagnetic waves. The inclined planes will also significantly reduce the true incident angle of electromagnetic waves relative to the metamaterial. The regular hexagonal holes on the top surface can cause additional secondary reflections at larger incident angles, especially for electromagnetic waves with shorter wavelengths.
[0009] 2. The microstructure of the aerogel material in the metamaterial of the present invention can excite a variety of polarization forms, such as electric dipole polarization, magnetic dipole polarization, etc. These different polarization modes have different response characteristics at different frequencies. When the frequency of the electromagnetic wave changes, different polarization modes will act sequentially or synergistically, so that the material can effectively interact with the electromagnetic wave in a wider frequency range; these microstructures in the metamaterial can also produce a variety of resonance phenomena. When multiple resonance frequencies are distributed in different frequency bands and overlap with each other, they can form strong absorption or scattering of electromagnetic waves in a very wide frequency range, greatly broadening the working bandwidth of the material; at the same time, the present invention can customize the design of metamaterials with specific absorbing properties according to specific application requirements, providing new ideas and methods for solving the problem of narrow working frequency band of materials.
[0010] Compared with the prior art, the advantages of the present invention are:
[0011] 1. Unique structural design: The material structure and thickness of each layer of the present invention are carefully designed. The introduction of the regular hexagonal blind hole structure on the top can achieve multiple scattering and reflection, while increasing the material's insensitivity to the angle of electromagnetic wave incidence; at the same time, the inclined side surface will increase the multiple reflections, refractions and scattering of electromagnetic waves inside the structure, so that the best synergy effect can be achieved between the layers, thus forming an "electromagnetic trap" with great affinity for electromagnetic waves; when electromagnetic waves pass through these stacked structures, they will be gradually guided, dispersed and absorbed, avoiding the problem of narrow absorption band caused by the excessive limitation of the resonance frequency of a single structure, and successfully achieving high-efficiency absorption and regulation of a wide band; the metamaterial structure designed by the present invention can expand EAB from 3.68GHz to 38GHz (2-40GHz);
[0012] 2. Broad application prospects: The preparation of the metamaterial designed by the present invention can adopt 3D printing or micro-nano processing technology, and at the same time combine the deposition and growth process of the material to achieve the precise construction of the microstructure unit in the main material, ensure the stability and consistency of the metamaterial performance, reduce production costs, and facilitate large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 FeNi prepared in step 3 of experiment 1 10 @Scanning electron microscopy image of NCA composite material;
[0014] Figure 2 Schematic diagram of the structure of the metamaterial constructed in step 5 of experiment 1;
[0015] Figure 3 The three-dimensional projection reflection loss spectrum of the porous carbon aerogel absorber calculated in step 4 of experiment one;
[0016] Figure 4 FeNi calculated for step 4 of experiment 1 10 @NCA's 3D projection reflection loss map;
[0017] Figure 5 This is a simulation result of the metamaterial constructed in step 5 of experiment 1;
[0018] Figure 6 This is a simulation result of the metamaterial constructed in step 5 of experiment 1;
[0019] Figure 7 This is a simulation result of the metamaterial constructed in step 5 of experiment 1;
[0020] Figure 8 Scanning electron microscopy (SEM) image of the VCA prepared in step 4 of experiment 2;
[0021] Fig. 9 The electromagnetic reflection loss data of the VCA calculated in step 5 of Experiment 2;
[0022] Fig.10 The three-dimensional projection reflection loss spectrum of the VCA calculated in step 5 of Experiment 2;
[0023] Fig.11 Schematic diagram of the structure of the metamaterial constructed in step 6 of experiment 2;
[0024] Fig.12 The simulation results of the metamaterial constructed in step 6 of Experiment 2;
[0025] Fig.13 The voltage standing wave ratio calculation diagram of the gradient metamaterial constructed in step 6 of experiment 2 and the single-layer material with the same thickness;
[0026] Fig.14 Schematic diagram of the structure of the metamaterial constructed in step 6 of experiment three;
[0027] Fig.15 This is a simulation result of the metamaterial constructed in step 6 of experiment three;
[0028] Fig.16 The voltage standing wave ratio calculation diagram of the gradient metamaterial constructed in step 6 of experiment three and the ordinary single-layer material of equal thickness. DETAILED DESCRIPTION
[0029] Specific implementation method 1: This implementation method is a broadband absorbing metamaterial with a topological gradient structure with robust characteristics, specifically, it is composed of a reflective layer located at the bottom and an absorbing layer located at the top, the absorbing layer is composed of three layers of gradient structure, the three layers of gradient structure are all regular tetrahedral structures and the bottom side length of the upper prism is smaller than the top side length of the lower prism, and the central axis of the three layers of gradient structure coincides; a regular hexagonal blind hole is set at the center of the upper surface of the absorbing layer, and the depth of the blind hole is less than the depth of the regular tetrahedral structure of the top layer; the absorbing layer is made of a mixture of aerogel material and paraffin.
[0030] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: in the three-layer gradient structure, the bottom side length L5 of the top prism is 8mm-23mm, and the top side length L6 of the top prism is 8mm-19mm; the bottom side length L3 of the middle prism is 9mm-25mm, and the top side length L4 of the middle prism is 9mm-22mm; the top side length L2 of the bottom prism is 12mm-26mm, and the bottom side length L1 of the bottom prism is 15mm-28mm. Others are the same as specific implementation method 1.
[0031] Specific implementation method 3: This implementation method is different from specific implementation method 1 in that the reflective layer is an electrically conductive layer and has a rectangular parallelepiped structure, and the horizontal cross section is a square and the side length is equal to the bottom side length L1 of the bottom prism in the three-layer gradient structure. The rest is the same as specific implementation method 1.
[0032] Specific embodiment 4: This embodiment differs from specific embodiment 1 in that the diameter of the circumscribed circle of the regular hexagonal blind hole is 1 mm to 5 mm, and the depth is 1 mm to 2 mm. Other aspects are the same as those of specific embodiment 1.
[0033] Specific implementation mode 5: This implementation mode is different from the specific implementation mode 1 in that the height of each layer in the three-layer gradient structure is 2 mm to 8 mm. The rest is the same as the specific implementation mode 1.
[0034] The present invention is verified by the following tests:
[0035] Test 1:
[0036] 1. In a glass bottle containing 4 mL of N,N-dimethylformamide, 0.0268 g of terephthalaldehyde, 0.01 g of scandium trifluoromethanesulfonate and 0.0468 g of 1,3,5-tris(4-aminophenyl)benzene were added in sequence, and the mixture was ultrasonicated until uniform. After ultrasonication for 5 minutes, it was allowed to stand and crystallize to form a COF gel. The COF gel was solvent exchanged with N,N-dimethylformamide, acetone, anhydrous ethanol, methanol and water in sequence, and the solvent was exchanged 3 times each time. The last water solvent was exchanged 5 times to obtain a COF hydrogel;
[0037] 2. Dissolve 0.2593 g of nickel chloride hexahydrate and 0.0.0295 g of ferric chloride hexahydrate in 4 mL of deionized water, and then add them to the COF hydrogel in step 1. The nickel and iron metal ions are adsorbed by the porous structure of the COF hydrogel. Let it stand for 5 days until the solution becomes colorless, and then freeze-dry for 12 hours to obtain FeNi 10 @COF aerogel;
[0038] 3. FeNi 10 @COF aerogel was placed on a quartz boat and moved into a tube furnace. It was kept at 800℃ in a nitrogen atmosphere for 2h at a heating rate of 2℃ / min and calcined to obtain FeNi 10 @NCA Composites;
[0039] 4. Prepare FeNi 10 The NCA composite material was immersed in melted paraffin to prepare a ring with an inner diameter of 3.04 mm and an outer diameter of 7 mm. 10 @NCA accounts for 10% of the total mass of the middle ring; FeNi 10@NCA electromagnetic parameters of the ring, according to the transmission line theory, the reflection loss of the material to the electromagnetic wave is calculated by the following equation;
[0040]
[0041] 5. Construction of FeNi 10 @NCA ring-based metamaterial: The electromagnetic parameters obtained by the vector network analyzer test are imported into the CST electromagnetic field simulation software, the frequency is set to 2-40GHz, the boundary is set to a periodic boundary, and the metamaterial is constructed. Specifically, it is composed of a reflective layer at the bottom and an absorbing layer at the top. The absorbing layer is composed of a three-layer gradient structure, and the three-layer gradient structure is a regular tetrahedral structure. The bottom side length of the upper prism is smaller than the top side length of the lower prism, and the central axis of the three-layer gradient structure coincides; a regular hexagonal blind hole is set at the center of the upper surface of the absorbing layer, the diameter L7 of the circumscribed circle of the regular hexagon is 3mm, and the hole depth H4 is 1mm; the depth of the blind hole is less than the depth of the top regular tetrahedral structure; such as Figure 2 As shown, the bottom bottom side length L1 of the trapezoidal structural unit is 27mm; the bottom side length L3 of the middle layer prism is 24mm; the bottom side length L5 of the top layer prism is 21mm; the top side length L2 of the bottom layer is 25mm; the top side length L4 of the middle layer prism is 22mm; the top side length L6 of the top layer prism is 18mm; the bottom layer height H1 of the trapezoidal structure is 4mm; the middle layer height H2 is 4mm, and the top layer prism height H3 is 5mm; the absorbing layer is a conductive layer, specifically an aluminum plate, with a thickness of 1mm and a horizontal size of 27mm×27mm; the excitation source is set to a Floquet port, two polarization modes (TE polarization and TM polarization) are set, and the electromagnetic wave incident angle Theta (0-80°) is set.
[0042] Test 2:
[0043] 1. Wash the rush powder through a 100-mesh sieve with water and anhydrous ethanol in turn, and dry it for later use; then disperse the rush powder (4 g) in a sodium hydroxide solution (100 mL, 5 wt%), stir at 80° C. for 4 h, and then wash with deionized water and anhydrous ethanol to remove residual impurities; then disperse the treated rush powder in 40 mL of a solution containing sodium chlorite (2 wt%) and acetic acid (0.3 mL), stir at 80° C. for 2 h, and obtain a white cellulose dispersion; finally, rinse with deionized water and anhydrous ethanol to obtain rush cellulose (JEC), and then dry it in an oven at 60° C.;
[0044] 2. Take 3mmoL of vanadium acetylacetonate and 3mmoL of terephthalic acid into a beaker, add 50mL of anhydrous ethanol to dissolve, and ultrasonicate for 30 minutes, then transfer the mixed solution to a stainless steel autoclave with a Teflon liner, and keep it at 180°C for 12 hours; cool to room temperature, wash with methanol, collect by filtration, and dry in an oven to obtain a gray-green V-MOF;
[0045] 3. Dissolve JEC in deionized water, stir and ultrasonicate to ensure a uniform solution; then add 1.5 g of V-MOF (the mass ratio of V-MOF:JEC is 1:2) to the above solution and mix well; quickly freeze the resulting mixture with liquid nitrogen and then freeze-dry for 48 hours to obtain V-MOF / JEC aerogel;
[0046] 4. Under N2 atmosphere, the V-MOF / JEC aerogel was placed in a tubular furnace for high temperature pyrolysis at 700℃ for 2h and naturally cooled to room temperature to obtain a rush / cellulose-derived carbon material composite material named VCA. The heating rate of the tubular furnace was 2℃·min -1 ;
[0047] 5. The prepared VCA electromagnetic wave absorbing material was immersed in melted paraffin to prepare a ring with an inner diameter of 3.04 mm and an outer diameter of 7 mm, wherein the mass of the VCA sample accounted for 12wt% of the total mass of the ring; the electromagnetic parameters of the VCA were measured by a vector network analyzer. According to the transmission line theory, the reflection loss of the material to the electromagnetic wave was calculated by the following equation:
[0048]
[0049] 6. Construct a metamaterial based on VCA: import the electromagnetic parameters of VCA obtained by the vector network analyzer test into the CST electromagnetic field simulation software, set the frequency to 2-40 GHz, set the boundary to a periodic boundary, and construct a metamaterial, specifically, a reflective layer located at the bottom and an absorbing layer located at the top, wherein the absorbing layer is composed of a three-layer gradient structure, all of which are regular tetrahedral structures, and the bottom side length of the upper prism is smaller than the top side length of the lower prism, and the central axis of the three-layer gradient structure coincides; a regular hexagonal blind hole is set at the center of the upper surface of the absorbing layer, the diameter L7 of the circumscribed circle of the regular hexagon is 3 mm, and the hole depth H4 is 1 mm; the depth of the blind hole is less than the depth of the regular tetrahedral structure of the top layer; such as Fig.11As shown, the bottom bottom side length L1 of the trapezoidal structural unit is 27mm; the bottom side length L3 of the middle layer prism is 24mm; the bottom side length L5 of the top layer prism is 21mm; the top side length L2 of the bottom layer is 25mm; the top side length L4 of the middle layer prism is 22mm; the top side length L6 of the top layer prism is 18mm; the bottom bottom height H1 of the trapezoidal structure is 7mm; the middle layer height H2 is 6mm, and the top layer prism height H3 is 7mm; the absorbing layer is a conductive layer, specifically an aluminum plate, with a thickness of 1mm and a horizontal size of 27mm×27mm.
[0050] Experiment 3: This experiment differs from Experiment 2 in that the frequency in step 6 is set to 2 to 18 GHz and the boundary is set to a periodic boundary; Fig.14 As shown, the absorbing layer is composed of three layers of gradient structure, the central axis of the three layers of gradient structure coincides; each layer is a rectangular parallelepiped structure and the horizontal cross section is a square, the bottom layer has a side length of 12mm and a thickness of 2mm; the middle layer has a side length of 9mm and a thickness of 2.5mm; the top layer has a side length of 8mm and a thickness of 2mm; the top layer surface is flat and has no holes. Others are the same as in Experiment 1.
[0051] Figure 1 FeNi prepared in step 3 of experiment 1 10 @The scanning electron micrograph of the NCA composite material shows that the COF-derived magnetic nitrogen-doped porous carbon aerogel is composed of regular nanospheres assembled into a pore structure with a size of about 320 nm, which are evenly distributed on the surface of the carbon microspheres and in the pores.
[0052] Figure 3 The three-dimensional projection reflection loss spectrum of the porous carbon aerogel absorber calculated in step 4 of experiment 1 shows that when the mass filling ratio is 10%, FeNi 10 @NCA exhibits excellent electromagnetic wave absorption performance, achieving minimum reflection loss (RL) at a ring thickness of 3.74 mm. min ) is -31.02dB.
[0053] Figure 4 FeNi calculated for step 4 of experiment 1 10 @NCA's three-dimensional projection reflection loss map shows that when the mass filling ratio is 10%, FeNi 10 @NCA exhibits excellent electromagnetic wave absorption performance. When the ring thickness is 3.74mm, the maximum effective absorption bandwidth (EAB max ) reaches 3.68GHz.
[0054] Figure 5 This is the simulation result of the metamaterial constructed in step 5 of experiment 1. The metamaterial exhibits excellent electromagnetic wave absorption performance. This gradient structure achieves an EAB of 38 GHz. max, covering the 2 to 40 GHz band.
[0055] Figure 6 This is the simulation result of the metamaterial constructed in step 5 of experiment 1. The metamaterial shows excellent frequency and angle insensitivity. Under TM polarization, within the angle range of 0 to 40°, this gradient structure can still achieve full-frequency absorption.
[0056] Figure 7 This is the simulation result of the metamaterial constructed in step 5 of experiment 1. The metamaterial shows excellent frequency and angle insensitivity. Under TE polarization, within the angle range of 0 to 50°, this gradient structure can still achieve full-frequency absorption.
[0057] Figure 8 The scanning electron microscope (SEM) image of the VCA prepared in step 4 of experiment 2 shows that the V2O3 microspheres are evenly distributed on the 3D aerogel matrix, with a porous structure and multiple heterogeneous interfaces. The porous VCA forms a larger 3D conductive network, increases the path for electron transfer, and causes electromagnetic waves to be scattered multiple times inside the material.
[0058] Fig. 9 The electromagnetic reflection loss data of VCA calculated in step 5 of Experiment 2 shows that when the mass filling ratio is 12%, VCA exhibits excellent electromagnetic wave absorption performance and achieves the minimum reflection loss (RL) when the ring is 2 mm thick. min ) is -63.92dB.
[0059] Fig.10 The three-dimensional projection reflection loss spectrum of VCA calculated in step 5 of experiment 2 shows that when the mass filling ratio is 12%, VCA exhibits excellent electromagnetic wave absorption performance. When the thickness is 2.44mm, EAB max Reaching 8.24GHz (9.76~18GHz), it covers almost half of the test frequency band.
[0060] Fig.12 This is the simulation result of the metamaterial constructed in step 6 of experiment 2. The metamaterial exhibits excellent electromagnetic wave absorption performance. This gradient structure achieves an EAB of 35.77 GHz. max , almost covering the 2~40GHz band.
[0061] Fig.13 This is the voltage standing wave ratio calculation diagram of the gradient metamaterial constructed in step 6 of experiment 2 and the ordinary single-layer material of equal thickness. The small figure is a local enlargement of the large figure. It can be seen that the voltage standing wave ratio (VSWR) value of the gradient structure is closer to 1 than that of the single-thickness structure, indicating better impedance matching.
[0062] Fig.15 This is the simulation result of the metamaterial constructed in step 6 of experiment 3. The metamaterial exhibits excellent electromagnetic wave absorption performance. This gradient structure achieves an EAB of 12.56 GHz. max , almost covering the 2-18 GHz band, but the effect is obviously not as good as Experiment 1 and Experiment 2.
[0063] Fig.16 This is the voltage standing wave ratio calculation diagram of the gradient metamaterial constructed in step 6 of experiment three and the ordinary single-layer material of equal thickness. It can be seen that the VSWR value of the gradient structure is closer to 1 than that of the single-thickness structure, indicating better impedance matching.
Claims
1. A broadband absorbing metamaterial with a robust topological gradient structure, characterized in that The broadband absorbing metamaterial with a topological gradient structure having robust characteristics is composed of a reflecting layer at the bottom and an absorbing layer at the top, wherein the absorbing layer is composed of three-layer gradient structures, all of which are regular tetrahedral structures, and the bottom side length of the upper prism is smaller than the top side length of the lower prism, and the central axes of the three-layer gradient structures coincide; a regular hexagonal blind hole is arranged at the center of the upper surface of the absorbing layer, and the depth of the blind hole is smaller than the depth of the regular tetrahedral structure of the top layer; and the absorbing layer is formed by mixing aerogel material and paraffin.
2. The broadband absorbing metamaterial with a robust topological gradient structure according to claim 1, characterized in that In the three-layer gradient structure: the bottom side length L5 of the top prism is 8mm~23mm, and the top side length L6 of the top prism is 8mm~19mm; the bottom side length L3 of the middle prism is 9mm~25mm, and the top side length L4 of the middle prism is 9mm~22mm; the top side length L2 of the bottom prism is 12mm~26mm, and the bottom side length L1 of the bottom prism is 15mm~28mm.
3. The broadband absorbing metamaterial with a robust topological gradient structure according to claim 1, characterized in that The reflective layer is an electrical conductive layer and has a rectangular parallelepiped structure. The horizontal cross section is a square and the side length is equal to the bottom side length L1 of the bottom prism in the three-layer gradient structure.
4. The broadband absorbing metamaterial with a robust topological gradient structure according to claim 1, characterized in that The diameter of the circumscribed circle of the regular hexagonal blind hole is 1 mm to 5 mm, and the depth is 1 mm to 2 mm.
5. The broadband absorbing metamaterial with a robust topological gradient structure according to claim 1, characterized in that The height of each layer in the three-layer gradient structure is 2mm to 8mm.
Citation Information
Patent Citations
Preparation method of CuHT-FCIP-EP composite material for wave-absorbing metamaterial and MOF-based wave-absorbing metamaterial
CN117844184A
Ultrathin broadband wave-absorbing metamaterial structure based on simple resistor surface
CN117878619A
Preparation method of magnetic nitrogen-doped porous carbon aerogel wave-absorbing material
CN118754102A
Cited By
Aerogel metamaterial capable of switching electromagnetic wave absorption and deflection reflection wave beam and preparation method thereof
CN120923856A